Drp1-dependent mitochondrial fission via MiD49/51 is essential for apoptotic cristae remodeling - Otera, Hidenori (J Cell Biol, 2016)
Mitochondrial fission facilitates cytochrome c release from the intracristae space into the cytoplasm during intrinsic apoptosis, although how the mitochondrial fission factor Drp1 and its mitochondrial receptors Mff, MiD49, and MiD51 are involved in this reaction remains elusive. Here, we analyzed the functional division of these receptors with their knockout (KO) cell lines. In marked contrast to Mff-KO cells, MiD49/MiD51-KO and Drp1-KO cells completely resisted cristae remodeling and cytochrome c release during apoptosis. This phenotype in MiD49/51-KO cells, but not Drp1-KO cells, was completely abolished by treatments disrupting cristae structure such as OPA1 depletion. Unexpectedly, OPA1 oligomers generally thought to resist cytochrome c release by stabilizing the cristae structure were similarly disassembled in Drp1-KO and MiD49/51-KO cells, indicating that disassembly of OPA1 oligomers is not directly linked to cristae remodeling for cytochrome c release. Together, these results indicate that Drp1-dependent mitochondrial fission through MiD49/MiD51 regulates cristae remodeling during intrinsic apoptosis.